PENGARUH GREEN ACCOUNTING, PENGUNGKAPAN ISLAMIC CORPORATE SOCIAL RESPONSIBILITY, DAN INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN. - Janatul Munawaroh; Dinda Fali Rifan; Nurhayati Nurhayati (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to analyze the influence of Green Accounting, Islamic Corporate Social Responsibility, and Intellectual Capital on the value of mining companies listed on the Indonesian Sharia Stock Index in 2019-2024. This study focuses on the growing need for sustainable business practices aligned with Sharia principles, as well as on the importance of transparency and resource efficiency in enhancing firm value in investors' eyes.Methods: This study uses quantitative research with a clause-associative approach, employing multiple linear analysis techniques, supported by SPSS software version 27. The study uses 87 company patterns and eight company samples, employing purposive sampling with specific sample criteria.Results: This study indicates that Green Accounting has a partial effect on firm value. In contrast, Islamic Corporate Social Responsibility has no significant effect on firm value, and Intellectual Capital has no effect on firm value. However, all three variables simultaneously influence firm value.Conclusion and suggestion: Based on the analytical findings tested, it can be concluded that Green Accounting has a partial positive effect on firm value. Meanwhile, Islamic Corporate Social Responsibility and intellectual capital have no significant effect on firm value. However, Green Accounting, Islamic Corporate Social Responsibility, and Intellectual Capital simultaneously influence firm value. Future researchers should expand the research period to provide a comprehensive overview of consistency. Furthermore, they could include other companies, not just mining companies, but also other sectors or non-Sharia companies. Adding variables and improving the research measurement methods could yield a more diverse set of firm values. Keywords: Company Value, Green Accounting, Intellectual Capital, Islamic Corporate, Social Responsibility